Perjanjian Bilateral Swap Agreement (BSA) Indonesia dengan Jepang dalam Sektor Keuangan dan Melakukan Perpanjangan Bilateral Swap Agreement (BSA) - Victor Hasiholan Sinurat; Tamaulina Sembiring (PT. PENERBIT TIGA MUTIARA, 2024)
The Bilateral Swap Agreement (BSA) aims to assist the financial sector by facilitating cooperation between Indonesia and Japan, providing developmental aid from the Japanese government to developing countries in the form of loans, yen loans, grants, and aid extended to Indonesia to stabilize the country's finances. This collaboration strengthens financial sectors and bilateral cooperation under the Bilateral Swap Agreement (BSA), implemented with the principle of pacta sunt servanda. Article 1320 explains the cooperation between Indonesia and Japan, where they extend agreements and enhance financial stability within a country, applying “lex specialis derogat legi generalis” agreements implemented by ministers and governors to recognize legally binding agreements between Indonesia and Japan, expanding the Bilateral Swap Agreement (BSA) framework in the financial sector. These agreements are advanced and legally recognized under established laws and regulations.